Magnitude and Distribution of Electricity and Water Subsidies for Households in Addis Ababa, Ethiopia - Cardenas, Helena; Whittington, Dale (World Bank, Washington, DC, 2019)
In Addis Ababa, an increasing block tariff has been used to calculate households' monthly bills for electricity and water services. This study estimates the magnitudes of the combined water and electricity subsidies received by households with private connections to the electricity grid and piped water network in 2016, and it evaluates the distribution of these subsidies among wealth groups. Customer billing data supplied by utility companies are matched with socioeconomic information collected through a household survey. It is the first detailed analysis of the combined effects of increasing block tariffs for electricity and water in an urban area in a developing country. The results show that the combined subsidies are large. The average household receives a subsidy of US$26 per month, about 6 percent of household income. The findings also show that electricity and water subsidies under the increasing block tariff disproportionately accrue to richer households, with even less targeting when both sectors are considered jointly. The poorest quintile receives 12 percent of the total subsidies for electricity and water services, while the richest quintile receives 31 percent. The water increasing block tariff's targeting of subsidies was somewhat worse than that of the electricity increasing block tariff.